Tobacco Policy: Prioritize State Revenue or Public Health - Nuphanudin Nuphanudin; Zakaria Zakaria; Muhammad Hermansyah; Ready Wicaksono; Fakhry Amin (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The Indonesian government has tried to make tobacco policy fair on many fronts. This is because even though the excise tax on tobacco provides a fairly high amount of revenue for the state, at the same time, the existence of tobacco has a negative health impact on the community. This research seeks to see how tobacco policy implementation affects state revenues and public health. The method used in this study is a descriptive qualitative approach. The data used in this research comes from various research results and previous studies regarding tobacco policy in Indonesia. The results of this study then found that tobacco control policies in Indonesia always experience development every year. This is because the government needs to devise a strategy that can be fair to all parties in the short and medium term. As for the long term, the government needs to find alternative solutions to tobacco excise revenue. This is because the tobacco policy's ultimate goal is to provide welfare for the people of Indonesia